EXPLORATION OF THE USE OF SCIENCE LEARNING MEDIA FOR BLIND STUDENTS AT SDLB NEGERI SEJAHTERA BOGOR CITY - Salsabila, Hasbiya; Suherman, Irman; Yektyastuti, Resti (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
Education is a basic need for everyone, including people with disabilities, who have the right to education. Children with visual impairments are usually called